Reality Therapy in Athletic Counseling: Applications for College Student-Athletes - Bartolini, Brian J. (My University, 1994)
Reality Therapy is a useful theoretical framework when working with the college student-athlete population. With its biological foundation in Control Theory, Reality Therapy offers an explanation of how and why human beings behave in this world and provides specific procedure to help client make positive change in their lives. This paper briefly outlined the major principles of Reality Therapy/Control Theory and applied them to some common issues facing college student-athletes (e.g., academic, career, athletic).
Keywords: theory; academic support